Series Solutions of Delay Integral Equations via a Modified Approach of Homotopy Analysis Method - Huseen, Shaheed N.; Tayih, Ali S. (Iraqi Journal of Science, 2021)
In this paper, the series solutions of a non-linear delay integral equations are considered by a modified approach of homotopy analysis method (MAHAM). We split the function into infinite sums. The outcomes of the illustrated examples are included to confirm the accuracy and efficiency of the MAHAM. The exact solution can be obtained using special values of the convergence parameter.